Gut microbiota and sepsis and sepsis-related death: a Mendelian randomization investigation - Shang, Weifeng; Zhang, Sheng; Qian, Hang; Huang, Sisi; Li, Hui; Liu, Jiao; Chen, Dechang (Frontiers in Immunology, 2024)
Background It is unclear what the causal relationship is between the gut microbiota and sepsis. Therefore, we employed Mendelian randomization (MR) to determine whether a causal link exists between the two. Methods This study used publicly available genome-wide association studies (GWAS) summary data of gut microbiota, sepsis, sepsis (critical care), and sepsis (28-day death in critical care) to perform a two-sample MR analysis. To ensure the robustness of the results, we also conducted a sensitivity analysis. Results For sepsis susceptibility, inverse variance weighted (IVW) estimates revealed that Victivallales (OR = 0.86, 95% CI, 0.78–0.94, p = 0.0017) was protective against sepsis, while Lentisphaerae (OR = 0.89, 95% CI, 0.80–0.99), Gammaproteobacteria (OR = 1.37, 95% CI, 1.08–1.73), Clostridiaceae1 (OR = 1.21, 95% CI, 1.04–1.40), RuminococcaceaeUCG011 (OR = 1.10, 95% CI, 1.01–1.20), Dialister (OR = 0.85, 95% CI, 0.74–0.97), and Coprococcus2 (OR = 0.81, 95% CI, 0.69–0.94) presented a suggestive association with the development of sepsis (all p < 0.05). For sepsis (critical care), IVW estimates indicated that Lentisphaerae (OR = 0.70, 95% CI, 0.53–0.93), Victivallales (OR = 0.67, 95% CI, 0.50–0.91), Anaerostipes (OR = 0.49, 95% CI, 0.31–0.76), LachnospiraceaeUCG004 (OR = 0.51, 95% CI, 0.34–0.77), and Coprococcus1 (OR = 0.66, 95% CI, 0.44–0.99) showed a suggestive negative correlation with sepsis (critical care) (all p < 0.05). For sepsis (28-day death in critical care), IVW estimates suggested that four bacterial taxa had a normally significant negative correlation with the risk of sepsis-related death, including Victivallales (OR = 0.54, 95% CI, 0.30–0.95), Coprococcus2 (OR = 0.34, 95% CI, 0.14–0.83), Ruminiclostridium6 (OR = 0.43, 95% CI, 0.22–0.83), and Coprococcus1 (OR = 0.45, 95% CI, 0.21–0.97), while two bacterial taxa were normally significantly positively linked to the risk of sepsis-related death, namely, Mollicutes (OR = 2.03, 95% CI, 1.01–4.08) and Bacteroidales (OR = 2.65, 95% CI, 1.18–5.96) (all p < 0.05). The robustness of the above correlations was verified by additional sensitivity analyses. Conclusion This MR research found that several gut microbiota taxa were causally linked to the risk of sepsis, sepsis in critical care, and sepsis-related 28-day mortality in critical care.